Kakawin Sutasoma / Mpu Tantular; Penerjemah, Dwi Woro R. Mastuti dan Hastho Bramantyo; Penyunting, Tim Sutasoma - MPU Tantular; DWI Woro R. Mastuti; HASTHO Bramantyo; TIM Sutasoma (Komunitas Bambu, 2009)
xxiv, 544 hlm. ; 21 cm.